Secreted Frizzled-Related Protein 2 (sFRP2) promotes osteosarcoma invasion and metastatic potential. Issue 1 (December 2016) - Techavichit, Piti; Gao, Yang; Kurenbekova, Lyazat; Shuck, Ryan; Donehower, Lawrence; Yustein, Jason
Abstract Background Osteosarcoma (OS), which has a high potential for developing metastatic disease, is the most frequent malignant bone tumor in children and adolescents. Molecular analysis of a metastatic genetically engineered mouse model of osteosarcoma identified enhanced expression of Secreted Frizzled-Related Protein 2 (sFRP2), a putative regulator of Wnt signaling within metastatic tumors. Subsequent analysis correlated increased expression in the human disease, and within highly metastatic OS cells. However, the role of sFRP2 in osteosarcoma development and progression has not been well elucidated. Methods Studies using stable gain or loss-of-function alterations of sFRP2 within human and mouse OS cells were performed to assess changes in cell proliferation, migration, and invasive ability in vitro, via both transwell and 3D matrigel assays. In additional, xenograft studies using overexpression of sFRP2 were used to assess effects on in vivo metastatic potential. Results Functional studies revealed stable overexpression of sFRP2 within localized human and mouse OS cells significantly increased cell migration and invasive ability in vitro and enhanced metastatic potential in vivo. Additional studies exploiting knockdown of sFRP2 within metastatic human and mouse OS cells demonstrated decreased cell migration and invasion ability in vitro, thus corroborating a critical biological phenotype carried out by sFRP2. Interestingly, alterations in sFRP2 expression did not alter OS proliferation rates or primary tumor development. Conclusions While future studies further investigating the molecular mechanisms contributing towards this sFRP2-dependent phenotype are needed, our studies clearly provide evidence that aberrant expression of sFRP2 can contribute to the invasive and metastatic potential for osteosarcoma.